The association between sleep duration and mortality: a review article - Alqahtani, Ali F.; Alqahtani, Ahmad F. (International Journal of Psychosocial Rehabilitation, 2020)
Abstract Objective: The aim of this review is to explore the association between sleep duration and all-cause mortality, and to investigate the associated risk with both short and long duration of sleep. Research design and method: A systemic review of publications performed using PUBMED, Google scholar, and manual search without language restrictions using keywords such as “sleep”, “sleep duration”, “mortality”, “insomnia”, and others. Results: Weselected15 cohort studies and two meta-analysis study that studied the association between sleep duration and all-cause and specific cause mortality. Findings from these studies showed an association between long and short sleeping hours in both men and women and mortality compared with who sleep between 7-8 hours daily. The consistent findings led us to draw U-shape relationship between sleep duration and all-cause mortality with the lowest point at 7-8 hours. Conclusion: Short and long sleep duration are both independent and significant factors of mortality.